2007
DOI: 10.1007/s11552-007-9061-3
|View full text |Cite
|
Sign up to set email alerts
|

“Sandwich” Plating for Intra-articular Distal Radius Fractures with Volar and Dorsal Metaphyseal Comminution

Abstract: Introduction Intra-articular distal radius fractures with volar and dorsal comminution present a special challenge to the hand surgeon. Methods Ten patients formed the study cohort. All plates were low profile and stainless steel. Radiographic parameters, range of motion, and strength compared to the uninjured side were recorded. Functional outcome was evaluated by Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire and Gartland and Werley scoring system. Results Median age at surgery was 58 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Day et al [20] reported the results of 12 patients who were treated by double plating, whose functional outcome were evaluated by DASH questionnaire and Gartland and Werley scoring system. They reported that 70% of the patients had good or excellent outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Day et al [20] reported the results of 12 patients who were treated by double plating, whose functional outcome were evaluated by DASH questionnaire and Gartland and Werley scoring system. They reported that 70% of the patients had good or excellent outcome.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,18 Dicpinigaitis et al 19 found that loss of reduction of volar tilt was observed for up to 6 months after EF, despite the use of pinning to secure the reduction. Various methods are available for treating these complex fractures.…”
Section: Discussionmentioning
confidence: 99%
“…They had similar results with one reported tendon rupture and one broken plate. Mudgal and Ring reported utilizing a T-plate and a DC plate secured together to allow adequate fixation of the distal fragment to the radial shaft [13], and Day et al described dorsal and volar sandwich plating [3]. While these techniques allow for better bony fixation, bridge plating mandates a second surgery for hardware removal to allow motion.…”
Section: Discussionmentioning
confidence: 99%
“…While previous volar, distal radial plates have had the ability to adequately control both intra-articular and/or juxta-articular fracture fragments [15, 17], their shaft length was not adequate to control both the articular surface and span extensive metadiaphyseal comminution while accommodating a typical radial bow. Other techniques, such as stacked plating [3, 13] and bridge plating [1, 6, 7, 18] have been recently described in an attempt to treat these difficult fractures; however, these techniques may utilize multiple plates and, at times, necessitate a secondary surgery for hardware removal [1, 6, 7, 18].…”
Section: Introductionmentioning
confidence: 99%